THE GLOBAL SCOURGE OF GUN VIOLENCE: A CALL FOR ACTION - Jadoon, Omair Khan; Salma Shazia,; Innayat Ullah,; Maimoona Haroon,; Adnan,; Fatima Inam, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Firearm injuries are critically important in criminal proceedings and jurisprudence discussions. The aim of the current study was to reinforce the growing concern of firearm violence in society and authenticate findings through autopsy examinations in the casualty department of Ayub Teaching Hospital Abbottabad. Method: This retrospective observational study was conducted in the casualty department of Ayub Teaching Hospital Abbottabad. Data was collected from registers spanning 1st September 2023 to 31st May 2024, after obtaining permission from the hospital administration. Result: Data from 56 cases were analyzed using SPSS 22. Among these, 50% suffered from firearm injuries, while the remaining 50% died due to sharp weapons, blunt weapons, poisoning, hanging, strangulation, road traffic accidents, electric shocks, or unknown causes. Of the total cases, 45 (80.4%) were male and 11 (19.6%) were female. The most affected age group was 20–40 years, comprising 36 (64.2%) cases. Furthermore, 42 (75%) cases were homicidal, 2 (3.6%) were suicidal, and 12 (21.4%) were accidental. Conclusion: The most common weapon used in homicidal deaths is firearms. Firearm violence should be prioritized as a critical issue in global health discussions.